PEMANFAATAN SISTEM INFORMASI GEOGRAFI DALAM PENGEMBANGAN PARIWISATA BAHARI DI BATAM, KEPULAUAN RIAU - Nasution, Nadia Widari; I Made Sondra Wijaya; Zainul Munir; Fiqri Ardi Azhari (JURNAL SITEBA, 2023)
Marine tourism in Batam, Riau Islands has great potential to be developed by utilizing Geographic Information Systems (GIS). This research aims to investigate the use of GIS in developing marine tourism in Batam, Riau Islands, by applying the System Development Life Cycle (SDLC) methodology. The SDLC methodology is used as a framework for developing and utilizing GIS that can improve the management and promotion of marine tourism in Batam. The SDLC stages include requirements analysis, design, implementation, verification and system maintenance. The results of this research show that the use of GIS with the SDLC approach can help improve the management and promotion of marine tourism in Batam. GIS applications enable users to obtain accurate and timely information about marine tourism attractions, assist in travel planning, and improve tourist experiences. By combining information technology and geographic data, marine tourism in Batam can continue to develop and become a major attraction for local and foreign tourists. Implementing the use of GIS with the SDLC methodology is a wise step to advance the marine tourism sector in Batam and the Riau Islands as a whole. Keywords: Marine tourism, GIS, SDLC, Batam.